ИНТЕРНЕТ КАК ИСТОЧНИК РАЗВИТИЯ НАУЧНО - ТВОРЧЕСКИХ СПОСОБНОСТЕЙ МОЛОДЁЖИ В ПРОЦЕССЕ НЕПРЕРЫВНОГО ОБРАЗОВАНИЯ - Назарова, Б. (SCIENCE and SOCIETY, 2017)
In the article the features of modern educational system are characterized. The role of the personality as the main value of process of training is defined. The importance of interaction of the teacher with information environment is emphasized. The main tasks of a professional educator in the synthesis of creative activities with the research have been defined.